First morphological and molecular report of needledscaled queenfish (Scomberoides tol) from Cilacap Waters, Penyu Bay, Indonesia - Muhammad Browijoyo Santanumurti; Sugeng Hartono; I Gede Suweda Anggana Putera; Laksmi Sulmartiwi; Sapto Andriyono; Heru Pramono; Veryl Hasan; Mohamed Abu El-Regal (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2026)
Fish misidentification often occurs in family Carangidae in Indonesia, especially genus Scomberoides, in Cilacap Waters. The condition can affect the fisheries management in the study area, because the management must be assessed to species level. The study aims to determine the physical characteristics and molecular information of the fish. Fish morphology was studied, tabulated, and documented according to its shape, colour, and general properties. Physical properties were measured and counted for morphometry and meristics study. DNA test was conducted to identify the species molecularly. DNA amplification method was polymerase chain reaction (PCR). The target gene used was the Cytochrome C Oxidase Subunit I (COI) gene. The primers used were FISH F1 and FISH R1. DNA sequencing used the Sanger dideoxy method. The fish was identified as Scomberoides tol physically with insignificant differences. There was no scutes and caudal peduncle groove in the fish. Its bases of anal and dorsal fin were equal in length. Finlets existed and semi–detached at posterior area to dorsal and anal fin. The type of scales and mouth was needle like and terminal, respectively. The fish shares 100% similarity of DNA with S. tol from previous studies across regions.